Analysis the suitability of e-storybook French children’s stories in learning French listening comprehension A2 CECRL - Lavrisha Rumanty Rachman; Tri Indri Hardini; Iis Sopiawati (Himpunan Pengembang Kurikulum Indonesia, 2026)
E-storybooks are a growing type of digital media for teaching French. They enable students to learn independently. An analysis was conducted to determine the suitability of the materials used in the developed media. The focus of this study was to analyze the suitability of materials in e-storybook French children’s stories for the F phase curriculum in learning French listening skills at level A2. The research was conducted using a qualitative approach with descriptive analysis. In this study, researchers found that children learned to listen to French stories at level A2 through e-storybook French children’s stories. The results showed that the materials presented in the e-storybook French children’s stories met the A2-level competency criteria based on CECRL, which were spread across various stories. The materials in the e-storybook French children’s stories aligned with the phase F curriculum for learning French listening skills at level A2. The materials in this media were delivered as audio narratives, animated videos, and narrative text stories, enabling students to engage in new learning experiences and learn independently. Abstrak E-storybook merupakan salah satu jenis media digital yang terus berkembang untuk mengajar bahasa Prancis. Media ini memungkinkan murid belajar secara mandiri. Analisis dilakukan untuk mengetahui kesesuaian materi yang digunakan dengan media yang dikembangkan. Fokus penelitian ini adalah menganalisis kesesuaian materi pada e-storybook French children’s stories dengan Kurikulum Fase F dalam pembelajaran keterampilan menyimak bahasa Prancis tingkat A2. Penelitian ini dilakukan dengan pendekatan kualitatif menggunakan analisis deskriptif. Dalam penelitian ini, peneliti menemukan bahwa anak-anak belajar menyimak cerita bahasa Prancis untuk level A2 melalui e-storybook French children’s stories. Hasil penelitian menunjukkan bahwa materi yang disajikan dalam e-storybook French children’s stories memenuhi kriteria kompetensi tingkat A2 berbasis CECRL yang tersebar dalam berbagai cerita. Materi dalam e-storybook French children’s stories menyajikan konten yang sesuai dengan kurikulum fase F dalam pembelajaran keterampilan menyimak bahasa Prancis tingkat A2. Materi pada media ini disampaikan dalam format narasi audio, video animasi, dan teks narasi cerita yang memungkinkan murid memperoleh pengalaman belajar baru serta belajar secara mandiri. Kata Kunci: e-storybook; keterampilan menyimak; materi pembelajaran bahasa Prancis